Efficacy of GnRH-Prostaglandin-GnRH Schedule in Management of Postpartum Anestrus and Subestrus Jafarabadi Buffaloes - Vijeyta, HP; Solanki, GB; Chaudhari, JK; Gamit, PM; Parikh, SS (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
Twelve postpartum Jafarabadi buffaloes of University farm were examined gynaecologically between months of February and May 2016 and were found to be either anestrus with smooth ovaries (n=8) or subestrous (n=4) with functional corpus luteum. All the 12 animals irrespective of ovarian status were injected i/m with Busreline acetate 20 µg (Receptal, 5 ml) on day 0, Cloprostenol 500 µg (2 ml) on day 7 and were inseminated twice after 72 and 84 hrs. Second injection of Receptal 2.5 ml was given at the time of 2nd insemination. Six buffaloes returned to estrous on 21st day following insemination which were reinseminated twice at 12 hours interval on reported estrous and injected with 2.5 ml Receptal. Pregnancy diagnosis was done two month post-insemination and conception rate of 50.00% (6/12) to first insemination and 33.33% (2/06) to second insemination was obtained. The overall conception rate obtained was 66.66% (8/12). Thus from the above facts, it can be said that this schedule of modified GnRH-PG-GnRH appears to work effectively in infertile Jafarabadi buffaloes with good conception rate.